Balanced Scorecard : A Case Study of Why Malaysian Companies are not for it? - Sukerathavan, Harichandran (2005)
The balanced scorecard arguably regarded as one of the most important and widely used financial framework. since it's creation by Robert Kaplan and David Norton, as a simple framework to resolve problems associated with traditional financial-only performance measurement system, the tool has evolved not only to become a comprehensive performance masurement framework but also a strategic management system.The general trend worldwide on the number of companies that have been implementing the Balanced Scorecard has been on a rise, but whether this is the same in a Malaysian context is difficult to determine, due to unavailability of supporting data and research. Under these circumstances, it probably would be fair to say that either Malaysian companies have been implementing the Balanced Scorecard (with no proper study done to determine the extent of implementation) or Malaysian companies are reluctance to implement the Balanced Scorecard. Based on the latter being the most likely case, a case study research was undertaken on two public-listed Malaysian companies to determine their reluctant in implementing the Balanced Scorecard. With an interview-based approach to undertake the case study, it was possible to conclude that Malaysian companies are well aware of the Balanced Scorecard concept and techniques, but their reluctance to implement the Balanced Scorecard was attributable to the cost,complexity, familiarity with their current measurement and planning tool and how the Balanced Scorecard would integrate with their current measurement system.Finally, it was also concluded that top management’s influence and support is a pre-requisite for the adoption and implementation of the Balanced Scorecard and the Balanced Scorecard is not that suitable for companies that operate in either a competitive or regulated environment.